A guide to indoor rock climbing injuries - Leung, J. (Current Sports Medicine Reports, 2023)
Rock climbing is an increasingly popular indoor sport with a sizable risk of overuse injuries. Yet, many medical practitioners have little familiarity with evaluating and treating climbing injuries because of the terminology, biomechanical demands, mechanisms of injury, and return to sport counseling needed, unique to the sport. This review seeks to educate practitioners on these aspects. Upper extremity injuries occur more frequently than lower extremity injuries, with finger injuries being most prevalent. Pulley injuries, consisting of rupture of the A2 or A4 annular pulleys are the most common type of injury. Other finger injuries include tenosynovitis of the flexor tendons, as well as lumbrical muscle tears. Elbow injuries occur frequently, with medial epicondylopathy being most common. Brachialis injuries are seldom seen outside of climbing. Lower-extremity injuries are typically more acute in nature, including ankle injuries from falls and knee injuries from strenuous climbing moves.